KORELASI MODAL TERHADAP KONTESTASI ARENA DAN PRAKTIK FEBA SUKMANA PENULIS NOVEL HOLLAND: ONE FINE DAY IN LEIDEN DALAM ASPEK PASAR, NARASI, DAN PENGGUNAAN BAHASA - Hary Sulistyo (POETIKA, 2015)
This research focuses to show Feba Sukmana’s modal implementation in narration and language use aspect. The first thing is about her cultural asset. She was born from art family and it made her likes reading stories and writing diary. The second asset is her Dutch insight when she studied in University of  Indonesia and master program in Leiden University. The third asset is about her habbit built since she was child, started from writing diary until writing Holland: One Fine Day In Leiden novel. The relation between educational background and language using is on the language choice. It is showed in the ability of  building narration, describing condition, using foreign language such as English and Dutch. Moreover, describing Dutch condition and concept  has so much relevance to the educational background. Keywords: Feba Sukmana, asset, the field of  contestation, and study and language relevance.